PEMBATALAN SERTIPIKAT HAK MILIK ATAS TANAH DALAM PRESPEKTIF JAMINAN KEPASTIAN DAN PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK ATAS TANAH: - Affan Zaidan; Listyowati Sumanto (Faculty of Law, Universitas Trisakti, 2023)
Land registration aims to guarantee legal certainty of land rights and legal protection for holders of rights to a plot of land—a certificate is a vital means of proof. The main problem is what causes the land title certificate to be canceled and what is the legal protection for land rights holders regarding land title certificates. The research method used is normative legal research, descriptive, analyzed qualitatively, and concluding using deductive logic. The results of the study show that certificates of land rights that have been issued in the name of the right holder can be requested to be canceled due to a court decision that has permanent legal force stating that it is void or does not have binding legal force or is due to administrative, legal defects due to errors in area calculations, object or subject errors, overlapping (dual certificates) including mistakes in the application of statutory regulations. Although land title certificates can still be canceled, if land registration is according to regulation, it can guarantee certainty and legal protection to land rights holders by presenting physical and juridical data in the certificate, which can be used as evidence when litigating in court.